ANALISIS PRINSIP 5C PADA PEMBIAYAAN KUR SEBAGAI UPAYA MEMINIMALISIR PEMBIAYAAN BERMASALAH (STUDI KASUS BSI KCP SURABAYA RUNGKUT 1) - Rista Izza Aminin; Toyyibatus Samsiah; Nurul Aulia Herlina Angganita; Siti Nur Azizah; Hafidz Akmal Khoirony; Muhammad Iqbal Surya Pratikto (Al-Iqtishad: Jurnal Ekonomi Syariah, 2025)
Indonesia's stable economic growth opens opportunities for people to access financing, especially through the KUR program that supports the Micro, Small and Medium Enterprises (MSMEs) sector. Bank Syariah Indonesia, as one of the largest Islamic banks, also provides KUR services to support the growth of MSMEs. However, behind the ease of access to financing, the risk of non-performing financing remains a challenge that must be anticipated. This research aims to analyze the application of the 5C principles in the KUR financing process at BSI KCP Surabaya Rungkut 1 and the extent to which these principles are effective in minimizing the risk of non-performing financing. The research method used is descriptive qualitative with primary data from in-depth interviews and secondary data from KUR financing documents, scientific literature, journals, and relevant previous research. The results showed that BSI KCP Surabaya Rungkut 1 applies the 5C principle thoroughly, including character, capacity, capital, collateral, and condition of economy as a reference in assessing customer eligibility. In addition, the post-disbursement monitoring process is carried out regularly through account monitoring and direct visits to business locations. The consistent application of the 5C principles has proven to help banks reduce the risk of non-performing financing while maintaining the quality of the KUR financing portfolio at BSI KCP Surabaya Rungkut 1.